SOCIODEMOGRAPHIC AND PHENOTYPIC CHARACTERISTICS AND RELATIONSHIP IN THE TEACHING OF GENETICS - Martins Ribeiro, Alessandro; Miranda Lago, Vivian (Health and Society, 2022)
The study evaluated the relationship of sociodemographic and phenotypic characters in relation to recessive and dominant factors of Mendelism in a population of students from a higher education institution. The teaching of genetics became co-responsible for explaining characteristics in individuals and for correlating the genetic mechanisms of heredity. The use of recreational activities, using the application of a perception form, promotes the implementation of observations of the expression of the genetic characters of individuals, allowing the identification of genotypes, giving students the ability to self-recognise inherited genes. Data collection took place in 2020, the students followed a script in order to observe certain characteristics such as: gender, ear lobe, eye color, skin color, hair type, anatomy of the lips and ability to curl the tongue, the study followed Resolutions 466/2012 and 510/2016. As a result, it was possible to explain the difference between recessive and dominant genes among students, in addition to stimulating learning, 21 students participated, (15), 71% were women and (06), 29% were men, 11 of the family members had the complete high school, 9 had no descendants; 13 had no knowledge of genetics. The dominant characters found were curly hair, thick lips and loose ear lobes, all of them are right-handed, represented by 16 of the 21 interviewees and as recessive characters only 01 had freckles on the face and 06 of the 21 had baldness. Playful activities in the teaching of genetics, such as perception forms, turn abstract concepts into practical experiences when they can be experienced.